Preparation method of copper powder enhanced terahertz composite wave-absorbing film
The preparation method of copper powder-reinforced terahertz composite absorbing film solves the problem that the existing thin film materials cannot cover the entire 6G frequency band, and achieves efficient electromagnetic wave absorption, meeting the electromagnetic compatibility requirements of 6G electronic devices.
Patent Information
- Application Number
- CN202511092572.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-05
- Publication Date
- 2026-01-02
AI Technical Summary
Existing technologies make it difficult to develop thin-film materials that can cover the entire 6G frequency band, and existing absorbing materials lack an effective correlation between thickness and absorption efficiency, which cannot meet the electromagnetic compatibility requirements of 6G electronic devices.
A copper powder-reinforced terahertz composite absorbing film was prepared by modifying alumina, coating with silica, and self-assembling copper powder, combined with polyurethane-modified epoxy resin adhesive, to produce a film with wide bandwidth and high absorption efficiency.
At the same thickness, the effective bandwidth and average absorption efficiency of the copper powder-reinforced terahertz composite absorbing film are significantly improved, achieving full-band absorption of the 0.3–3.0 THz frequency band and meeting the requirements of 6G technology.
Smart Images

Figure CN121248980A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the field of electronic materials, and particularly relates to a preparation method of a copper powder reinforced terahertz composite wave-absorbing film. BACKGROUND
[0002] The International Telecommunication Union has defined the frequency band of 0.3 THz-3 THz as terahertz radiation, which is smaller than the original definition and is more suitable for 6G communication applications (Wang Zhanjiang, Li Kailei, Zhang Feixiang, et al. Terahertz communication technology for 6G. Mobile Communications, 2025, 49(5): 121-127.).
[0003] Electromagnetic shielding materials are key materials for 6G technology (Zhu Hongwei. New materials in the 6G era. Nature Journal, 2023, 45(2): 109-112.). Electromagnetic shielding has two types, one is the reflection of electromagnetic waves, for most electromagnetic shielding materials, as long as the reflection efficiency is ≥3 dB, the reflectivity is ≥50%; the other is the absorption of electromagnetic waves. The reflection of electromagnetic waves will cause secondary pollution of stray electromagnetic waves, and cannot achieve complete protection, while the absorption of electromagnetic waves can avoid the above problems.
[0004] Reflective electromagnetic wave type materials can be very thin, to the micron level, but absorption electromagnetic wave type materials are generally thicker, usually in the millimeter level. Although the increase in thickness can improve the wave absorption efficiency to some extent, it is more to move the absorption peak to the low frequency direction, and there is no corresponding relationship between thickness and wave absorption efficiency.
[0005] According to the principle of impedance matching, the better the impedance matching with air, the lower the reflection of electromagnetic waves, and vice versa, the reflection is enhanced, and the wave absorption efficiency is definitely weakened, so impedance matching is the preferred principle for designing wave-absorbing electromagnetic shielding materials (Wang Daoyuan, Gao Chengzhe, Huang Wanxia, et al. Terahertz wave reflection regulation based on silicon-based MXene film layer impedance regulation. Laser and Optoelectronics Progress, 2023, 60(18): 1811017.).
[0006] The impedance matching degree of metal materials with air is low, and metal is usually a reflective electromagnetic wave type; but if metal is used as a reflection center and surrounded by wave-absorbing materials, the loss path of electromagnetic waves in the material can be prolonged, thereby improving the wave absorption efficiency of the material. Therefore, the use of metal and other non-metallic wave-absorbing materials in cooperation is expected to obtain new materials with higher wave-absorbing performance, but the research on how to design new materials with metal as the raw material and develop new processes is scattered and not systematic, and cannot provide meaningful guidance.
[0007] For wave-absorbing materials, the effective bandwidth is usually defined by the frequency range with an absorption efficiency of less than or equal to -10 dB. For 6G technology, the frequency range is 0.3-3 THz. Currently, there is a lack of thin film materials with effective bandwidth covering the full frequency range of 6G, which limits the development of 6G electronic devices.
[0008] The present application aims to solve the above problems, and provides a preparation method of a copper powder enhanced terahertz composite wave-absorbing film. Compared with the film without copper powder, the key performance indicators of the composite wave-absorbing film, such as the minimum wave-absorbing efficiency, effective bandwidth and average wave-absorbing efficiency, are greatly improved, which is innovative. SUMMARY
[0009] The present application aims to provide a preparation method of a copper powder enhanced terahertz composite wave-absorbing film, which provides new materials for electromagnetic compatibility and wave-absorbing electromagnetic protection of 6G electronic devices.
[0010] The preparation method of the copper powder enhanced terahertz composite wave-absorbing film provided by the present application comprises the following steps:
[0011] (1) Alumina modification: alumina powder with a particle size of 50-150 nm is placed in a silane coupling agent solution, stirred at room temperature for 30-50 minutes, then poured into a centrifuge tube, placed in a centrifuge at a speed of 3000-5000 rpm for 10-20 minutes, the supernatant is poured out, filtered, and dried to obtain silane coupling agent modified alumina; wherein the solute of the silane coupling agent solution is any one of 3-mercaptopropyl trimethoxysilane, mercaptopropyl methyl dimethoxysilane, vinyl-tris(2-methoxyethoxy)silane, gamma-(2,3-epoxypropoxy) propyl trimethoxysilane, and N-beta-aminoethyl-gamma-aminopropyl trimethoxysilane, and the solvent is any one of acetone, methyl ethyl ketone, tetrahydrofuran, and 1,4-dioxane, with a mass percentage concentration of 3-5%; wherein the weight ratio of alumina powder to silane coupling agent solution is 1:(15-25);
[0012] (2) Silica coating: chitin powder with a mesh size of 100-200 is added to an aqueous hydrochloric acid solution, heated to 40-60℃, stirred for 2-3 hours, filtered, the filtrate is cooled to 0℃, filtered, the solid is washed with ice water, and dried to obtain chitin nanocrystals; the chitin nanocrystals are added to deionized water, ultrasonically dispersed for 30-50 minutes, then 100-300 nm silica powder is added, ultrasonically dispersed for another 30-50 minutes, then stirred for 1-2 hours, filtered, and dried to obtain chitin coated silica; wherein the mass percentage concentration of the aqueous hydrochloric acid solution is 5-10%; wherein the weight ratio of chitin powder to aqueous hydrochloric acid solution is 1:(20-30); wherein the weight ratio of chitin nanocrystals, deionized water and silica powder is 1:(50-60):(5-8);
[0013] (3) Copper powder self-assembly: copper powder with a particle size of 50-100 nm is added into hydrochloric acid aqueous solution, stirred for 3-5 minutes, filtered, and the solid is washed with deionized water, ethanol and ether in sequence, and then dried in a vacuum oven. Then the dried copper powder is added into a substituted benzene sulfenol solution, stirred at room temperature for 6-8 hours, filtered and dried to obtain substituted benzene sulfenol self-assembled nano copper powder. The concentration of the hydrochloric acid aqueous solution is 5%-10%. The weight ratio of the copper powder with a particle size of 50-100 nm to the hydrochloric acid aqueous solution is 1:(10-15). The solute of the substituted benzene sulfenol solution is any one of p-aminobenzene sulfenol, p-hydroxybenzene sulfenol, p-chlorobenzene sulfenol and p-dimethylamino benzene sulfenol, and the solvent is any one of tetrahydrofuran, dimethyl sulfoxide and N,N-dimethylformamide, and the mass percentage concentration is 1%-3%. The weight ratio of the dried copper powder to the substituted benzene sulfenol solution is 1:(30-40).
[0014] (4) Preparation of a composite wave-absorbing film: the silane coupling agent modified alumina in step (1) is added into polyurethane modified epoxy resin glue, stirred for 20-30 minutes, then the chitin coated silica in step (2) is added, stirred for 20-30 minutes, then the substituted benzene sulfenol self-assembled nano copper powder in step (3) is added, stirred for 10-20 minutes, then the curing agent hydroxyethyl ethylenediamine and the dispersing agent polyvinyl alcohol are added in sequence, and the stirring is continued for 1-2 hours to obtain a mixed solution. Then the mixed solution is poured into a coating machine, coated and dried to obtain a copper powder enhanced terahertz composite wave-absorbing film. The weight ratio of the polyurethane modified epoxy resin glue, the silane coupling agent modified alumina, the chitin coated silica, the substituted benzene sulfenol self-assembled nano copper powder, the hydroxyethyl ethylenediamine and the polyvinyl alcohol is 1:(0.3-0.5):(0.3-0.5):(0.3-0.5):(0.1-0.2):(0.2-0.4). The thickness of the copper powder enhanced terahertz composite wave-absorbing film is 0.5-2.0 mm.
[0015] The method for testing the wave-absorbing performance of the composite wave-absorbing film when used for electromagnetic protection is as follows: the copper powder enhanced terahertz composite wave-absorbing film is cut into a size of 2 cm*2 cm, placed into a clamp, and then placed into a terahertz time domain spectroscopy system to test the electromagnetic wave absorbing efficiency of the composite wave-absorbing film in a frequency range of 0.3-3.0 THz in transmission mode and reflection mode.
[0016] It is measured that the lowest wave-absorbing efficiency of the film with a thickness of 1 mm in a frequency range of 0.3-3.0 THz reaches-26.7 dB, and the effective bandwidth with a wave-absorbing efficiency less than-10 dB is the whole frequency range.
[0017] The present application has the following advantages:
[0018] (1) Compared with the composite absorbing film prepared by the present invention, the effective bandwidth, minimum absorption efficiency and average absorption efficiency are greatly improved at the same thickness (1 mm).
[0019] (2) The composite absorbing film prepared by the present invention can achieve full-band 6G technology absorption, with significant technical effects.
[0020] (3) Structural innovation: by utilizing the electromagnetic wave reflection properties of copper powder, terahertz electromagnetic waves are diffusely reflected in the composite absorbing film, thus extending the loss path.
[0021] (4) Modifying the raw materials enriches the types of functional groups, which enhances the absorption effects such as polarization relaxation, vibration relaxation, and valence resonance, expands the absorption bandwidth, and improves the absorption effect.
[0022] The University of Electronic Science and Technology of China (UESTC) has disclosed a multifunctional terahertz absorbing fabric based on MXenes material and its preparation method (Announcement No.: CN118087282B). This invention addresses the problems of narrow absorption bandwidth, limited functionality, and susceptibility to oxidation inherent in MXenes absorbing materials. Based on the fiber microstructure within the matrix, and combining the conductivity and ohmic losses of MXenes material, water-based polyurethane (WPU) is sprayed onto the surface of the absorbing fabric for modification, resulting in a multifunctional terahertz absorbing material with an absorption efficiency of 100% in the 0.3–1.2 THz electromagnetic wave range. The MXenes material used in this invention is very expensive, hindering its widespread adoption. The raw materials used in this invention are readily available, the preparation process is simple, and the technology is more mature. The prepared absorbing film has an effective bandwidth of 0.3–3.0 THz, representing a wider bandwidth.
[0023] Sichuan Jiuzhou Electric Group Co., Ltd. disclosed a flexible terahertz absorbing composite material and its preparation method (Announcement No.: CN117467277A), comprising: incorporating activated graphene powder into three-dimensional graphene to obtain a three-dimensional composite material; completely impregnating the three-dimensional composite material into a polydimethylsiloxane precursor, impregnating under vacuum conditions, and then heating and curing to obtain the flexible terahertz absorbing composite material. The core of this invention is three-dimensional graphene, while the core of this invention is nano-copper powder. The two have different material systems, different preparation methods, and different terahertz absorbing mechanisms. Attached Figure Description
[0024] Figure 1 This is a scanning electron microscope (SEM) image of the copper powder-reinforced terahertz composite absorbing film prepared in Example 1.
[0025] Figure 2The image shows the elemental analysis of the copper powder-reinforced terahertz composite absorbing film prepared in Example 1 using energy dispersive X-ray spectroscopy.
[0026] Figure 3 The following diagrams show the terahertz absorption performance: (1) is an alumina composite film with a thickness of 1 mm prepared in Comparative Example 1; (2) is a silicon dioxide composite film with a thickness of 1 mm prepared in Comparative Example 2; and (3) is a copper powder reinforced terahertz composite absorbing film with a thickness of 1 mm prepared in Example 1. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments.
[0028] Example 1
[0029] (1) Alumina modification: Alumina powder with a particle size of 50-150 nm was placed in a silane coupling agent solution and stirred at room temperature for 30 minutes. Then it was poured into a centrifuge tube and centrifuged at 3000 rpm for 10 minutes. The supernatant was discarded, filtered, and dried to obtain silane coupling agent modified alumina. The solute of the silane coupling agent solution was 3-mercaptopropyltrimethoxysilane, the solvent was acetone, and the mass percentage concentration was 3%. The weight ratio of alumina powder to silane coupling agent solution was 1:15.
[0030] (2) Silica coating: Chitosan powder of 100-200 mesh was added to hydrochloric acid aqueous solution, heated to 40°C, stirred for 2 hours, filtered, the filtrate was cooled to 0°C, filtered again, the solid was washed with ice water and dried to obtain chitosan nanocrystals; chitosan nanocrystals were added to deionized water and ultrasonically dispersed for 30 minutes, then silica powder with a particle size of 100-300 nm was added, ultrasonically dispersed for another 30 minutes, stirred for 1 hour, filtered, and dried to obtain chitosan-coated silica; wherein, the mass percentage concentration of hydrochloric acid aqueous solution was 5%, the weight ratio of chitosan powder to hydrochloric acid aqueous solution was 1:20; the weight ratio of chitosan nanocrystals, deionized water and silica powder was 1:50:5;
[0031] (3) Copper powder self-assembly: Copper powder with a particle size of 50-100 nm was added to hydrochloric acid aqueous solution, stirred for 3 minutes, filtered, and the solid was washed successively with deionized water, ethanol and diethyl ether, and then dried in a vacuum oven. Then the dried copper powder was added to a substituted thiophenol solution, stirred at room temperature for 6 hours, filtered, and dried to obtain substituted thiophenol self-assembled nano copper powder; wherein, the concentration of hydrochloric acid aqueous solution was 5%; the weight ratio of copper powder with a particle size of 50-100 nm to hydrochloric acid aqueous solution was 1:10; the solute of the substituted thiophenol solution was p-aminothiophenol, the solvent was tetrahydrofuran, and the mass percentage concentration was 1%; the weight ratio of the dried copper powder to the substituted thiophenol solution was 1:30.
[0032] (4) Preparation of composite absorbing film: Add the silane coupling agent modified alumina from step (1) to the polyurethane modified epoxy resin adhesive, stir for 20 minutes, then add the chitin-coated silica from step (2), stir for 20 minutes, then add the substituted thiophenol self-assembled nano copper powder from step (3), stir for 10 minutes, then add the curing agent hydroxyethyl ethylenediamine and the dispersant polyvinyl alcohol in sequence, continue stirring for 1 hour to obtain a mixture, then pour the mixture into a coating machine, coat, and dry to obtain a copper powder reinforced terahertz composite absorbing film; wherein, the weight ratio of polyurethane modified epoxy resin adhesive, silane coupling agent modified alumina, chitin-coated silica, substituted thiophenol self-assembled nano copper powder, hydroxyethyl ethylenediamine and polyvinyl alcohol is 1:0.3:0.3:0.3:0.1:0.2; the thickness of the copper powder reinforced terahertz composite absorbing film is 1 mm.
[0033] Example 2
[0034] (1) Alumina modification: Alumina powder with a particle size of 50-150 nm was placed in a silane coupling agent solution and stirred at room temperature for 50 minutes. Then it was poured into a centrifuge tube and centrifuged at 5000 rpm for 20 minutes. The supernatant was discarded, filtered, and dried to obtain silane coupling agent modified alumina. The solute of the silane coupling agent solution was mercaptopropylmethyldimethoxysilane, the solvent was methyl ethyl ketone, and the mass percentage concentration was 5%. The weight ratio of alumina powder to silane coupling agent solution was 1:25.
[0035] (2) Silica coating: Chitosan powder of 100-200 mesh was added to hydrochloric acid aqueous solution, heated to 60°C, stirred for 3 hours, filtered, the filtrate was cooled to 0°C, filtered, the solid was washed with ice water and dried to obtain chitosan nanocrystals; chitosan nanocrystals were added to deionized water and ultrasonically dispersed for 50 minutes, then silica powder with a particle size of 100-300 nm was added, ultrasonically dispersed for another 50 minutes, stirred for 2 hours, filtered, and dried to obtain chitosan-coated silica; wherein, the mass percentage concentration of hydrochloric acid aqueous solution was 10%; the weight ratio of chitosan powder to hydrochloric acid aqueous solution was 1:30; the weight ratio of chitosan nanocrystals, deionized water and silica powder was 1:60:8;
[0036] (3) Copper powder self-assembly: Copper powder with a particle size of 50-100 nm was added to hydrochloric acid aqueous solution, stirred for 5 minutes, filtered, and the solid was washed successively with deionized water, ethanol and diethyl ether, and then dried in a vacuum oven. Then the dried copper powder was added to a substituted thiophenol solution, stirred at room temperature for 8 hours, filtered, and dried to obtain substituted thiophenol self-assembled nano copper powder; wherein, the concentration of hydrochloric acid aqueous solution was 10%; the weight ratio of copper powder with a particle size of 50-100 nm to hydrochloric acid aqueous solution was 1:15; the solute of the substituted thiophenol solution was p-hydroxythiophenol, the solvent was dimethyl sulfoxide, and the mass percentage concentration was 3%; the weight ratio of the dried copper powder to the substituted thiophenol solution was 1:40.
[0037] (4) Preparation of composite absorbing film: Add the silane coupling agent modified alumina from step (1) to the polyurethane modified epoxy resin adhesive, stir for 30 minutes, then add the chitin-coated silica from step (2), stir for 30 minutes, then add the substituted thiophenol self-assembled nano copper powder from step (3), stir for 20 minutes, then add the curing agent hydroxyethyl ethylenediamine and the dispersant polyvinyl alcohol in sequence, continue stirring for 2 hours to obtain a mixture, then pour the mixture into a coating machine, coat, and dry to obtain a copper powder reinforced terahertz composite absorbing film; wherein, the weight ratio of polyurethane modified epoxy resin adhesive, silane coupling agent modified alumina, chitin-coated silica, substituted thiophenol self-assembled nano copper powder, hydroxyethyl ethylenediamine and polyvinyl alcohol is 1:0.5:0.5:0.5:0.2:0.4; the thickness of the copper powder reinforced terahertz composite absorbing film is 0.5 mm.
[0038] Example 3
[0039] (1) Alumina modification: Alumina powder with a particle size of 50-150 nm was placed in a silane coupling agent solution and stirred at room temperature for 30 minutes. Then it was poured into a centrifuge tube and centrifuged at 5000 rpm for 10 minutes. The supernatant was discarded, filtered, and dried to obtain silane coupling agent modified alumina. The solute of the silane coupling agent solution was vinyl-tris(2-methoxyethoxy)silane, the solvent was tetrahydrofuran, and the mass percentage concentration was 3%. The weight ratio of alumina powder to silane coupling agent solution was 1:25.
[0040] (2) Silica coating: Chitosan powder of 100-200 mesh was added to hydrochloric acid aqueous solution, heated to 40°C, stirred for 3 hours, filtered, the filtrate was cooled to 0°C, filtered again, the solid was washed with ice water and dried to obtain chitosan nanocrystals; chitosan nanocrystals were added to deionized water and ultrasonically dispersed for 30 minutes, then silica powder with a particle size of 100-300 nm was added, ultrasonically dispersed for another 50 minutes, stirred for 1 hour, filtered, and dried to obtain chitosan-coated silica; wherein, the mass percentage concentration of hydrochloric acid aqueous solution was 10%; the weight ratio of chitosan powder to hydrochloric acid aqueous solution was 1:20; the weight ratio of chitosan nanocrystals, deionized water and silica powder was 1:60:5;
[0041] (3) Copper powder self-assembly: Copper powder with a particle size of 50-100 nm was added to hydrochloric acid aqueous solution, stirred for 3 minutes, filtered, and the solid was washed successively with deionized water, ethanol and diethyl ether, and then dried in a vacuum oven. Then the dried copper powder was added to a substituted thiophenol solution, stirred at room temperature for 8 hours, filtered, and dried to obtain substituted thiophenol self-assembled nano copper powder; wherein, the concentration of hydrochloric acid aqueous solution was 5%; the weight ratio of copper powder with a particle size of 50-100 nm to hydrochloric acid aqueous solution was 1:10; the solute of the substituted thiophenol solution was p-chlorothiophenol, and the solvent was any one of N,N-dimethylformamide, with a mass percentage concentration of 3%; the weight ratio of the dried copper powder to the substituted thiophenol solution was 1:40.
[0042] (4) Preparation of composite absorbing film: Add the silane coupling agent modified alumina from step (1) to the polyurethane modified epoxy resin adhesive, stir for 20 minutes, then add the chitin-coated silica from step (2), stir for 30 minutes, then add the substituted thiophenol self-assembled nano copper powder from step (3), stir for 10 minutes, then add the curing agent hydroxyethyl ethylenediamine and the dispersant polyvinyl alcohol in sequence, continue stirring for 2 hours to obtain a mixture, then pour the mixture into a coating machine, coat, and dry to obtain a copper powder reinforced terahertz composite absorbing film; wherein, the weight ratio of polyurethane modified epoxy resin adhesive, silane coupling agent modified alumina, chitin-coated silica, substituted thiophenol self-assembled nano copper powder, hydroxyethyl ethylenediamine and polyvinyl alcohol is 1:0.3:0.5:0.3:0.2:0.2; the thickness of the copper powder reinforced terahertz composite absorbing film is 2.0 mm.
[0043] Example 4
[0044] (1) Alumina modification: Alumina powder with a particle size of 50-150 nm was placed in a silane coupling agent solution and stirred at room temperature for 40 minutes. Then it was poured into a centrifuge tube and centrifuged at 4000 rpm for 15 minutes. The supernatant was discarded, filtered, and dried to obtain silane coupling agent modified alumina. The solute of the silane coupling agent solution was γ-(2,3-epoxypropoxy)propyltrimethoxysilane, the solvent was 1,4-dioxane, and the mass percentage concentration was 4%. The weight ratio of alumina powder to silane coupling agent solution was 1:20.
[0045] (2) Silica coating: Chitosan powder of 100-200 mesh was added to hydrochloric acid aqueous solution, heated to 50°C, stirred for 3 hours, filtered, the filtrate was cooled to 0°C, filtered again, the solid was washed with ice water and dried to obtain chitosan nanocrystals; chitosan nanocrystals were added to deionized water and ultrasonically dispersed for 40 minutes, then silica powder with a particle size of 100-300 nm was added, ultrasonically dispersed for another 40 minutes, stirred for 1 hour, filtered, and dried to obtain chitosan-coated silica; wherein, the mass percentage concentration of hydrochloric acid aqueous solution was 8%; the weight ratio of chitosan powder to hydrochloric acid aqueous solution was 1:25; the weight ratio of chitosan nanocrystals, deionized water and silica powder was 1:55:7;
[0046] (3) Copper powder self-assembly: Copper powder with a particle size of 50-100 nm was added to hydrochloric acid aqueous solution, stirred for 4 minutes, filtered, and the solid was washed successively with deionized water, ethanol and diethyl ether, and then dried in a vacuum oven. Then the dried copper powder was added to a substituted thiophenol solution, stirred at room temperature for 7 hours, filtered, and dried to obtain substituted thiophenol self-assembled nano copper powder; wherein, the concentration of hydrochloric acid aqueous solution was 8%; the weight ratio of copper powder with a particle size of 50-100 nm to hydrochloric acid aqueous solution was 1:12; the solute of the substituted thiophenol solution was p-dimethylaminothiophenol, the solvent was tetrahydrofuran, and the mass percentage concentration was 2%; the weight ratio of the dried copper powder to the substituted thiophenol solution was 1:35.
[0047] (4) Preparation of composite absorbing film: Add the silane coupling agent modified alumina from step (1) to the polyurethane modified epoxy resin adhesive, stir for 25 minutes, then add the chitin-coated silica from step (2), stir for 25 minutes, then add the substituted thiophenol self-assembled nano copper powder from step (3), stir for 15 minutes, then add the curing agent hydroxyethyl ethylenediamine and the dispersant polyvinyl alcohol in sequence, continue stirring for 2 hours to obtain a mixture, then pour the mixture into a coating machine, coat, and dry to obtain a copper powder reinforced terahertz composite absorbing film; wherein, the weight ratio of polyurethane modified epoxy resin adhesive, silane coupling agent modified alumina, chitin-coated silica, substituted thiophenol self-assembled nano copper powder, hydroxyethyl ethylenediamine and polyvinyl alcohol is 1:0.4:0.3:0.4:0.2:0.3; the thickness of the copper powder reinforced terahertz composite absorbing film is 1.5 mm.
[0048] Example 5
[0049] (1) Alumina modification: Alumina powder with a particle size of 50-150 nm was placed in a silane coupling agent solution and stirred at room temperature for 35 minutes. Then it was poured into a centrifuge tube and centrifuged at 5000 rpm for 12 minutes. The supernatant was discarded, filtered, and dried to obtain silane coupling agent modified alumina. The solute of the silane coupling agent solution was N-β-aminoethyl-γ-aminopropyltrimethoxysilane, the solvent was acetone, and the mass percentage concentration was 5%. The weight ratio of alumina powder to silane coupling agent solution was 1:18.
[0050] (2) Silica coating: Chitosan powder of 100-200 mesh was added to hydrochloric acid aqueous solution, heated to 60°C, stirred for 2 hours, filtered, the filtrate was cooled to 0°C, filtered again, the solid was washed with ice water and dried to obtain chitosan nanocrystals; chitosan nanocrystals were added to deionized water and ultrasonically dispersed for 35 minutes, then silica powder with a particle size of 100-300 nm was added, ultrasonically dispersed for another 45 minutes, stirred for 2 hours, filtered, and dried to obtain chitosan-coated silica; wherein, the mass percentage concentration of hydrochloric acid aqueous solution was 5%; the weight ratio of chitosan powder to hydrochloric acid aqueous solution was 1:30; the weight ratio of chitosan nanocrystals, deionized water and silica powder was 1:50:6;
[0051] (3) Copper powder self-assembly: Copper powder with a particle size of 50-100 nm was added to hydrochloric acid aqueous solution, stirred for 5 minutes, filtered, and the solid was washed successively with deionized water, ethanol and diethyl ether, and then dried in a vacuum oven. Then the dried copper powder was added to a substituted thiophenol solution, stirred at room temperature for 7 hours, filtered, and dried to obtain substituted thiophenol self-assembled nano copper powder; wherein, the concentration of hydrochloric acid aqueous solution was 7%; the weight ratio of copper powder with a particle size of 50-100 nm to hydrochloric acid aqueous solution was 1:12; the solute of the substituted thiophenol solution was p-aminothiophenol, the solvent was N,N-dimethylformamide, and the mass percentage concentration was 3%; the weight ratio of the dried copper powder to the substituted thiophenol solution was 1:35.
[0052] (4) Preparation of composite absorbing film: Add the silane coupling agent modified alumina from step (1) to the polyurethane modified epoxy resin adhesive, stir for 25 minutes, then add the chitin-coated silica from step (2), stir for 20 minutes, then add the substituted thiophenol self-assembled nano copper powder from step (3), stir for 20 minutes, then add the curing agent hydroxyethyl ethylenediamine and the dispersant polyvinyl alcohol in sequence, continue stirring for 2 hours to obtain a mixture, then pour the mixture into a coating machine, coat, and dry to obtain a copper powder reinforced terahertz composite absorbing film; wherein, the weight ratio of polyurethane modified epoxy resin adhesive, silane coupling agent modified alumina, chitin-coated silica, substituted thiophenol self-assembled nano copper powder, hydroxyethyl ethylenediamine and polyvinyl alcohol is 1:0.5:0.4:0.5:0.1:0.2; the thickness of the copper powder reinforced terahertz composite absorbing film is 1.0 mm.
[0053] Comparative Example 1
[0054] (1) Alumina modification: Alumina powder with a particle size of 50-150 nm was placed in a silane coupling agent solution and stirred at room temperature for 30 minutes. Then it was poured into a centrifuge tube and centrifuged at 3000 rpm for 10 minutes. The supernatant was discarded, filtered, and dried to obtain silane coupling agent modified alumina. The solute of the silane coupling agent solution was 3-mercaptopropyltrimethoxysilane, the solvent was acetone, and the mass percentage concentration was 3%. The weight ratio of alumina powder to silane coupling agent solution was 1:15.
[0055] (2) Preparation of alumina composite film: Add the silane coupling agent modified alumina from step (1) to the polyurethane modified epoxy resin adhesive, stir for 20 minutes, then add the curing agent hydroxyethyl ethylenediamine and the dispersant polyvinyl alcohol in sequence, continue stirring for 1 hour to obtain a mixture, then pour the mixture into a coating machine, coat, and dry to obtain an alumina composite film; wherein, the weight ratio of polyurethane modified epoxy resin adhesive, silane coupling agent modified alumina, hydroxyethyl ethylenediamine and polyvinyl alcohol is 1:0.3:0.1:0.2; the thickness of the alumina composite film is 1 mm.
[0056] Comparative Example 2
[0057] (1) Alumina modification: Alumina powder with a particle size of 50-150 nm was placed in a silane coupling agent solution and stirred at room temperature for 30 minutes. Then it was poured into a centrifuge tube and centrifuged at 3000 rpm for 10 minutes. The supernatant was discarded, filtered, and dried to obtain silane coupling agent modified alumina. The solute of the silane coupling agent solution was 3-mercaptopropyltrimethoxysilane, the solvent was acetone, and the mass percentage concentration was 3%. The weight ratio of alumina powder to silane coupling agent solution was 1:15.
[0058] (2) Silica coating: Chitosan powder of 100-200 mesh was added to hydrochloric acid aqueous solution, heated to 40°C, stirred for 2 hours, filtered, the filtrate was cooled to 0°C, filtered again, the solid was washed with ice water and dried to obtain chitosan nanocrystals; chitosan nanocrystals were added to deionized water and ultrasonically dispersed for 30 minutes, then silica powder with a particle size of 100-300 nm was added, ultrasonically dispersed for another 30 minutes, stirred for 1 hour, filtered, and dried to obtain chitosan-coated silica; wherein, the mass percentage concentration of hydrochloric acid aqueous solution was 5%, the weight ratio of chitosan powder to hydrochloric acid aqueous solution was 1:20; the weight ratio of chitosan nanocrystals, deionized water and silica powder was 1:50:5;
[0059] (3) Preparation of silica composite film: Add the silane coupling agent modified alumina from step (1) to the polyurethane modified epoxy resin adhesive, stir for 20 minutes, then add the chitosan-coated silica from step (2), stir for 20 minutes, then add the curing agent hydroxyethyl ethylenediamine and the dispersant polyvinyl alcohol in sequence, continue stirring for 1 hour to obtain a mixture, then pour the mixture into a coating machine, coat, and dry to obtain a silica composite film; wherein, the weight ratio of polyurethane modified epoxy resin adhesive, silane coupling agent modified alumina, chitosan-coated silica, hydroxyethyl ethylenediamine and polyvinyl alcohol is 1:0.3:0.3:0.1:0.2; the thickness of the silica composite film is 1 mm.
[0060] The microwave absorption performance testing method for the thin films prepared in Examples 1-5 and Comparative Examples 1-2 is as follows (refer to: Hou Shengkai. Composite Terahertz Absorbing Material Based on MXene. Master's Thesis of University of Electronic Science and Technology of China, 2024): The thin film is cut into 2cm×2cm pieces, placed in a fixture, and then placed in a terahertz time-domain spectroscopy system. The electromagnetic wave absorption efficiency of the composite absorbing thin film in the frequency range of 0.3-3.0THz is tested using transmission mode and reflection mode.
Claims
1. A method for preparing a copper powder-reinforced terahertz composite absorbing thin film, characterized in that: (1) Alumina modification: Alumina powder with a particle size of 50~150nm is placed in a silane coupling agent solution and stirred at room temperature for 30~50 minutes. Then it is poured into a centrifuge tube and centrifuged at 3000~5000rpm for 10~20 minutes. The supernatant is discarded, filtered, and dried to obtain silane coupling agent modified alumina. The solute of the silane coupling agent solution is any one of 3-mercaptopropyltrimethoxysilane, mercaptopropylmethyldimethoxysilane, vinyl-tris(2-methoxyethoxy)silane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and N-β-aminoethyl-γ-aminopropyltrimethoxysilane. The solvent is any one of acetone, methyl ethyl ketone, tetrahydrofuran, and 1,4-dioxane. The mass percentage concentration is 3%~5%. The weight ratio of alumina powder to silane coupling agent solution is 1:(15~25). (2) Silica coating: Chitosan powder of 100-200 mesh is added to hydrochloric acid aqueous solution, heated to 40-60℃, stirred for 2-3 hours, filtered, the filtrate is cooled to 0℃, filtered, the solid is washed with ice water and dried to obtain chitosan nanocrystals; chitosan nanocrystals are added to deionized water, ultrasonically dispersed for 30-50 minutes, then silica powder with a particle size of 100-300 nm is added, ultrasonically dispersed for another 30-50 minutes, stirred for 1-2 hours, filtered, and dried to obtain chitosan-coated silica; wherein, the mass percentage concentration of hydrochloric acid aqueous solution is 5%-10%; wherein, the weight ratio of chitosan powder to hydrochloric acid aqueous solution is 1:(20-30); wherein, the weight ratio of chitosan nanocrystals, deionized water and silica powder is 1:(50-60):(5-8); (3) Copper powder self-assembly: Copper powder with a particle size of 50~100nm is added to hydrochloric acid aqueous solution, stirred for 3~5 minutes, filtered, and the solid is washed with deionized water, ethanol and ether in sequence, and then placed in a vacuum oven to dry. Then the dried copper powder is added to substituted thiophenol solution, stirred at room temperature for 6~8 hours, filtered, and dried to obtain substituted thiophenol self-assembled nano copper powder; wherein, the concentration of hydrochloric acid aqueous solution is 5%~10%; wherein, the weight ratio of copper powder with a particle size of 50~100nm to hydrochloric acid aqueous solution is 1:(10~15); wherein, the solute of substituted thiophenol solution is any one of p-aminothiophenol, p-hydroxythiophenol, p-chlorothiophenol, p-dimethylaminothiophenol, and the solvent is any one of tetrahydrofuran, dimethyl sulfoxide, N,N-dimethylformamide, and the mass percentage concentration is 1%~3%; wherein, the weight ratio of dried copper powder to substituted thiophenol solution is 1:(30~40). (4) Preparation of composite microwave absorbing film: Add the silane coupling agent modified alumina from step (1) to the polyurethane modified epoxy resin adhesive, stir for 20-30 minutes, then add the chitin-coated silica from step (2), stir for 20-30 minutes, then add the substituted thiophenol self-assembled nano copper powder from step (3), stir for 10-20 minutes, then add the curing agent hydroxyethyl ethylenediamine and the dispersant polyvinyl alcohol in sequence, continue stirring for 1-2 hours to obtain a mixture, and then pour the mixture into a coating machine. Coating and drying yield a copper powder-reinforced terahertz composite absorbing film; wherein the weight ratio of polyurethane-modified epoxy resin adhesive, silane coupling agent-modified alumina, chitosan-coated silica, substituted thiophenol self-assembled nano-copper powder, hydroxyethyl ethylenediamine and polyvinyl alcohol is 1:(0.3~0.5):(0.3~0.5):(0.3~0.5):(0.1~0.2):(0.2~0.4); wherein the thickness of the copper powder-reinforced terahertz composite absorbing film is 0.5~2.0 mm.
2. The copper powder-reinforced terahertz composite absorbing film according to claim 1, characterized in that, The method for testing its absorption performance when used for electromagnetic protection is as follows: cut the copper powder reinforced terahertz composite absorbing film into 2cm×2cm size, place it in a fixture, and then place it in a terahertz time-domain spectroscopy system. Use transmission mode and reflection mode to test the electromagnetic wave absorption efficiency of the copper powder reinforced terahertz composite absorbing film in the frequency range of 0.3~3.0 THz.
Citation Information
Patent Citations
Flexible terahertz wave-absorbing composite material and preparation method thereof
CN117467277A
A multifunctional terahertz absorbing fabric based on MXenes materials and its preparation method
CN118087282B
Cited By
Preparation method of wave-absorbing electromagnetic shielding film for 6G electronic device
CN121949984A